Allantoin accumulation mediated by allantoinase down-regulation and transport by Ureide Permease 5 (UPS5) confers salt stress tolerance to Arabidopsis plants - Lescano, C. I. (2015)
Fil: Lescano, C. I. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.